Le foncier pastoral au Sahel, des mobilités fragilisées - Alexis Gonin (Bulletin de l’Association de Géographes Français)
The success of Sahelian pastoralism is based on mobility (transhumance and nomadism). Historically, the mobility is protected by a system of commons which allowed access to resources for all. However, latest changes have jeopardized pastoral mobility.